Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Produk H Group Indonesia di Kota Bima - Jumaidin Jumaidin; Muhajirin Muhajirin (Journal of Business and Economics Research (JBE), 2020)
This study intends to determine the effect of product quality on consumer satisfaction H GROUP INDONESIA KIMA BIMA products. The type of research used is associative. This research was conducted on consumers of H GROUP INDONESIA in Bima City whose target is consumers who have been shopping for H Group Indonesia Bima City products. The technique for taking the sample used was the accidental sampling method with 55 respondents. Data analysis techniques used are simple linear regression, simple correlation coefficient, coefficient of determination, correlation coefficient and partial test (t test). Based on the results of the study showed that: product quality variables have an effect on consumer satisfaction in the H Group Indonesia Bima City